Dwarf galaxies as hosts of stellar explosions: gas kinematics and abundances in 3D. Issue Volume 14:Issue S344(2019) (August 2018) - Thöne, C. C.; Izzo, L.; Flores, H.; Vergani, S.; Christensen, L.
Abstract: The hosts of long Gamma-ray bursts (GRBs) are places of intense star-formation, which, at low redshift, are primarily low-mass dwarf starburst galaxies. Spatially resolved studies of these galaxies are still sparse, even more so at high spectral resolution where we can probe gas kinematics, in- and outflows and differences in abundance between different components. Here we present the first high resolution IFU sample of six low redshift GRB hosts, all dwarf starbursts. All galaxies in our sample show evidence for excess emission or broad emission components, with velocities of 100-200 km s −1 . For GRB 030329, outflowing gas had also been observed in absorption in spectra of the GRB afterglow. The high velocity emission is usually blue shifted, connected to the brightest star-forming regions and more metal rich than the narrow component associated with the emission of the general host ISM. This gives strong indications that the excess emission/broad component is indeed associated to a starburst wind as observed in many field star-burst galaxies and a sign for the intense ongoing star-formation in those galaxies.